Fatty Liver and Liver Malondialdehyde Expression in Severe Malnourished Wistar Rats that given Virgin Coconut oil Compared to Corn Oil in World Health Organization Formula - I Gusti Ayu Putu Eka Pratiwi; Soetjiningsih .; I N. Mantik Astawa; I Gusti Ayu Trisna Windiani; I Gede Ngurah Harry Wijaya Surya (Journal of Global Pharma Technology, 2017)
Objective: There is a lack of antioxidant in severe malnutrition, and it may lead to increase oxidative stress. Fatty liver is one of severe malnutrition (SM) cardinal features. Virgin coconut oil (VCO) contains high antioxidant capacity and medium chain triglyceride. It is supposed to improve those problems. Methods: Posttest only control group design study was done to observe whether VCO could decrease fatty liver and liver malondialdehyde (MDA) expression in 38 male wistar rat with SM. The rats were divided into two group which were VCO Group (Group A) and Control Group (corn oil (Group B)). They were given feeding World Health Organization (WHO) Formula for SM (Formula 75 and Formula 100) that contained VCO or corn oil. After being SM, this formula was fed until 28 days. In the 29th day, they were sacrificed, and liver samples were obtained for fatty liver analysis and MDA expression. Results: Fatty liver was less in Group A (mean 13.74 cell in 5 view field (SD 1.32) than Group B (mean 20.74 cell in 5 view field (SD 2.01), and it was statistically significant (p=0.000). Cut off point for determining low and high liver MDA expression based on o ROC curve were <2.9% (low) and ≥2.9% (high). Low MDA expression (<2.9%) was higher in Group A than Group B (p <0.05). Conclusions: This study found less fatty liver and low liver MDA expression in severe malnourished rat given VCO than corn oil. Keywords: Virgin coconut oil, Fatty liver, Malondialdehyde, Severe malnutrition.